An investigation of vortex breakdown at Mach 2 - Craven, A. H.; Alexander, A. J. (College of Aeronautics, 1963)
Wind tunnel tests have been made at M = 2 on a 75° swept delta wing in order to study the progressive breakdown of the leading edge vortices, which occurs at high incidence. The incidence at which vortex breakdown occurred at supersonic speeds was somewhat less than at low speeds, but the pattern of breakdown appeared to be similar, although the spiralling region of flow is much larger at supersonic speeds. Quite slender objects placed downstream of the wing had appreciable upstream effects, causing vortex breakdown to move upstream by as much as 20% of the root chord for the same incidence.